Microbial Profile and Dental Caries in Cleft Lip and Palate Babies Between 0 and 3 Years Old - YILMAZ, MÜESSER AHU (ALLIANCE COMMUNICATIONS GROUP DIVISION ALLEN PRESS, 2019)
Objective: The aim of this study was to examine the microbiological changes in newborn babies with cleft lip palate from birth up to age 3 and to correlate them with their caries levels and mothers' microbiological data and to compare with normal infants. Basic Research Design: Prospective. Settings: Marmara University, Faculty of Dentistry, Pediatric Dentistry Clinic, and Sili Hamidiye Etfal Education and Research Hospital New Born Clinic. Patients/Participants: Cleft lip palate (n = 21) and healthy (n = 13) newborns and their mothers. Material and Methods: Intraoral samples were taken from babies in each group at least 3 times over the 3 years. Saliva samples of the mothers were collected just after the birth of the babies and examined microbiologically. Dental caries was noted as either present or absent. Results: The most frequent microorganisms were candida, found at birth (n = 9, 42%) in cleft palate with or without cleft lip (CP +/- L) group. The number of babies infected with Lactobacilli were found to be significantly higher in the CP +/- L group than in the control group at birth (P = .029) and after eruption of the first primary tooth (P = .030). Mutans Streptococci were found in 10% of babies with CP +/- L at birth. Initial caries was identified in 20% of the babies with an oral cleft compared with 0% of the controls after eruption of the first primary incisors. Conclusion: The results show that the CP +/- L babies must be considered as a group with an increased caries risk.
Keywords: dental health; microbiology; maternal factors; EARLY-CHILDHOOD CARIES; MUTANS STREPTOCOCCI; ORAL-HEALTH; AND/OR PALATE; CHILDREN; PREVALENCE; COLONIZATION; TRANSMISSION; ASSOCIATION; INFANTS